ERGONOMIC INTERVENTION OF HOUSES TYPE 36/120 SAVES ELECTRICITY AND INCREASES COMFORT OF OCCUPANTS IN NUANSA KORI HOUSING SADING MENGWI BADUNG - Parwata, I Wayan; Manuaba, Adnyana; Adiputra, Nyoman; Sutjana, IDP (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
Development of the housing sector has now spread to the suburban areas ofDenpasar; even some rural areas in Bali have become targets of housingdevelopers. Designing and arranging of houses through ergonomic interventioncomprises one of several efforts for improving the houses’ quality in terms oftheir natural comfort. The ergonomic intervention should meet such criteria as tobe technically applicable, less costly, energy saving especially that of electricity,socio-culturally convenience, and environment friendly. This experimental studybeing reported applied a treatment by subject design, in which eight houses wereselected as sample, located in the housing complex of Perumahan Nuansa KoriSading Mengwi Badung. Of the eight sampled houses, each two houses facednorth, south, east and west, respectively. Twenty six occupants of the eightsampled houses were interviewed using a questionnaire. All samples wereselected by stratified random sampling. The ergonomic intervention comprisedremodeling of ventilation and windows of all the sampled houses. Data collectingof objective comfort was carried out before and after intervention i.e. at 8 am, 10am, 12 pm, 2 pm, 4 pm and 8 pm, by measuring temperature, humidity, lightintensity, and airflow. Data of subjective comfort were collected by questionnaire,which had been tested earlier for its validity and reliability. The results showedthat (1) before intervention the average of wet temperature was 23.66 ± 1.36 ºC,after intervention was 23.09 ± 1.20 ºC; (2) before intervention the average of drytemperature was 28.76 ± 1.07 ºC, after intervention was 27.88 ± 0.73 ºC; (3)relative humidity before intervention was 73.44 ± 4.37 %, after intervention was72.63 ± 2.73 %; (4) natural light intensity before intervention was 134.94 ± 71.69lux, after intervention was 229.69 ± 114.53 lux; (5) the average of airflow beforeintervention was 0.10 ± 0.04 m/sc, after intervention was 0.31 ± 0.08 m/sc; and(6) electricity saving resulted in 11% as evidenced by decrease of electricity billby 8%. The conclusions could be arawn are (1) that ergonomic intervention byremodeling ventilation and windows of houses type 36/120 could improveobjective comfort by 12.4% (p<0.05), along with increase of subjective comfort ofthe occupants of the houses facing all directions; dan (2) moreover, electricitysaving resulted in 11% (p<0.05) as evidenced by decrease of electricity bill by 8%(p<0.05). This study suggests that ergonomic intervention should be applied sinceearly in the construction of houses in order to make them cheaper, healthier, andmore comfortable.
Keywords: Ergonomic intervention, house type 36/120, comfort, electricity saving.